Bcl-2 phosphorylation and implications in apoptosis in cancer cells - Xia, Yan (2011)
Bcl-2 is the central regulator in apoptosis. Structural studies of Bcl-2 reveal a flexible loop flanking the Bcl-2 homology domain 3 (BH3) and BH4. In response to external stimuli, several kinases phosphorylate the loop of Bcl-2. Phosphorylation on Bcl-2 has been thought to affect the protein’s activity in apoptosis as well as autophagy. However, the molecular basis and mechanistic details of Bcl-2 phosphorylation still remains a mystery. To further define and better understand the biological significance and the regulation of Bcl-2 through phosphorylation, we focus on changes in molecular interaction, using a phospho-mimetic Bcl-2 as a model. Our structural analysis indicates phosphorylation would induce conformational change in the flexible loop of Bcl-2. Binding study revealed phospho-mimetic Bcl-2 has decreased affinity to pro-apoptotic protein Bak. Based on our result, we hypothesized the structural-function relationship for Bcl-2 phosphorylation.